A practitioner's guide to rational-emotive behavior therapy - DiGiuseppe, Raymond; Doyle, Kristene A.; Dryden, Windy; Backx, Wouter (Oxford University Press, 2014)
Designed for both therapists-in-training and seasoned professionals, this practical treatment guide introduces the basic principles of rational-emotive behaviour therapy, explains general therapeutic strategies, and offers many illustrative dialogues between therapist and patient. It breaks down each stage of therapy to present the exact procedures and skills therapists need, and numerous case studies illustrate how to use these skills.